The single nucleotide polymorphism rs700518 is an independent risk factor for metabolic syndrome and benign prostatic hyperplasia (MetS‐BPH). (5th June 2018) - Chen, Z.P.; Yan, Y.; Chen, C.J.; Li, M.; Chen, C.; Zhao, S.C.; Song, T.; Liu, T.; Zou, C.H.; Xu, Q.; Li, X.
Summary: Studies have shown that 48.59% of benign prostate hyperplasia (BPH) is combined with metabolic syndrome (MetS). The mainstream view supports the correlation between MetS and BPH, but the pathogenesis of MetS‐BPH is not fully understood. Four hundred and seventy‐four men, aged 47 years or older, were recruited into this study by consecutive routine physical examination programs, and several parameters were obtained from each participant. Based on the diagnosis of BPH, MetS, and MetS‐BPH, the participants were divided into BPH and Non‐BPH groups, MetS and Non‐MetS groups, as well as MetS‐BPH and Non‐MetS‐BPH groups. The values of the obtained parameters were evaluated using Student's t ‐test, chi‐square test, and logistic regression analysis. The value of estradiol (E2) was higher in the diseased groups (BPH, MetS, and MetS‐BPH groups) compared with the corresponding control groups (Non‐BPH, Non‐MetS, and Non‐MetS‐BPH groups), and the differences were statistically significant. Also, E2 had an independent association with BPH (OR = 2.286, 95% CI: 1.723–3.593, p  <   0.001), MetS (OR = 1.406, 95% CI: 0.585–2.315, p  <   0.001), and MetS‐BPH (OR = 1.249, 95% CI: 0.795–1.962, p  <   0.001). Regarding SNPs of CYP19A1 gene, both the rs4646 genotypes (CC, CA, and AA) and the rs700518 genotypes (CC, CT, and TT) were present in every group, and all genotypes had statistically significant differences between the diseased and corresponding control groups. However, only the TT genotype of rs700518 was independently associated with BPH, MetS, and MetS‐BPH after adjusting for age. The TT genotype of rs700518 is an independent risk factor for the MetS‐BPH populations, and the CYP19A1 gene regulation of estrogen leads to MetS‐BPH.